Effect of normobaric hyperoxia on gentamicin-induced nephrotoxicity in rats - Tavafi, Majid (Mashhad University of Medical Sciences, 2014)
OBJECTIVE(S): Gentamicin sulphate (GS) nephrotoxicity seems to be related to the generation of reactive oxygen species. There is evidence that oxygen preconditioning increases the activity of antioxidant enzymes. MATERIALS AND METHODS: Forty eight female rats were divided into 6 groups (n=8) as follows: group 1 was the control, group 2 received daily GS, groups 3,4 and 5 received oxygen 2 hr/day for 2 days, 4 hr/day for 2 days, 4 hr/day for 4 days, recpectively and then received daily GS, group 6 received oxygen 2 hr/day for 2 days and then received 2 hr oxygen before daily GS injection. Oxygen (with 90% purity) used at the flow rate of 4 l/min. GS administred for 8 days (100 mg/kg, IP). Tissue sections prepared from the left kidney, stained with PAS method and then studied hisopathologically and stereologically. The right kidneys were homogenized and the supernatants were prepared. Serum MDA, creatinine and urea, renal MDA, gluthatione and catalase activity were measured. The data were analyzed by Mann-Whitney U test at the significant level of P<0.05. RESULTS: Oxygen therapy significantly improves serum creatinine and urea, preserve tubular volume density, reduce tubular necrosis in groups 4 and 6 compared to group 2. Oxygen therapy significantly increases renal catalase in groups 4 and 6 compared to group 2. CONCLUSION: Pretreatment with normobaric hyperoxia and daily oxygen therapy improved gentamicin nephrotoxicity possibly via inhibition of lipid peroxidation and increasing the renal catalase activity but could not restore any parameter at the same levels as control group.